Effective Implementation of Culturally Appropriate Tools in Addressing Overweight and Obesity in an Urban Underserved Early Childhood Population in Pediatric Primary Care. (May 2019) - Herbst, Rachel Becker; Khalsa, Amrik Singh; Schlottmann, Haley; Kerrey, Mary Kathleen; Glass, Katherine; Burkhardt, Mary Carol
Overweight and obese children are at an increased risk of remaining obese. The American Academy of Pediatrics recommends addressing healthy habits at well-child checks, but this poses challenges, especially in low-income populations. A clinical innovation project was designed to adapt recommendations in a busy urban clinic and consisted of motivational interviewing, culturally tailored tools, and standardizing documentation. A quasi-experimental design examined innovation outcomes. Of 137 overweight and obese children aged 24 to 66 months, providers' documentation of weight during well-child check visits improved post-innovation ( P < .01), as did development of healthy habits goals ( P < .001). Families were more likely to return for visits post-innovation ( P = .01). A logistic regression analysis showed that adding body mass index to the problem list and establishing a specific follow-up timeframe most predicted follow-up visits to assess progress ( P < .001). Comprehensive innovations consisting of motivational interviewing, implementation of culturally tailored tools, and standardized documentation can enhance engagement in an urban clinic setting.